Design by Optimization on the Nozzle and the Stator Blades of a Rim-Driven Pumpjet - Marco Lugaresi; Diego Villa; Stefano Gaggero (Journal of Marine Science and Engineering)
The design of the stator and nozzle of a rim-driven pumpjet thruster (RDPJ) is addressed through a simulation-based design optimization approach built on a parametric description of the main geometrical characteristics of the system, a RANS solver with actuator disk model, and a genetic algorithm. As the propeller blades’ geometry is fixed, the rotor/stator (RDPJ-R/S) configuration is considered for the optimal design from a multi-objective optimization process aimed at minimizing the resistance keeping the cavitation inception index at the lowest possible value. Steady-state (moving reference frame plus mixing plane interface) and unsteady simulations (sliding meshes) with fully resolved rotor geometry were finally carried out on six selected optimal geometries to validate the optimization process and the performance improvements provided by the RDPJ configuration when compared with the original rim-driven thruster (RDT).